Site Assessment for Astroparticle Detector Location in Evaporites of the Polkowice-Sieroszowice Copper Ore Mine, Poland - Jaroslaw Slizowski; Zenon Pilecki; Kazimierz Urbanczyk; Elzbieta Pilecka; Leszek Lankof; Rafal Czarny (Advances in High Energy Physics)
The aim of the work was to evaluate the possibilities of excavating a chamber for the Glacier detector, a cylinder with a 74 m diameter and 38 m height filled with 100 kT of liquid argon, in the Polkowice-Sieroszowice copper ore mine in the Legnica-Glogow Copper Area (LGOM). Two potential locations were analyzed in a rock salt layer more than 100 m thick at the depth of 1000 m and in the anhydrite layer of about 100 m thick at the depth of 650 m, both lying above the copper ore deposit. The numerical analyses, based on geological, geophysical, and geomechanical research, were carried out to determine the behavior of the system of the chamber and surrounding rock mass. Two creep laws have been adopted for rock salt in the numerical models, Norton and Lubby2. Their coefficients have been adjusted for in situ measurements of the mine galleries convergence starting from the results of laboratory tests. Displacement and stresses of the rock salt in the chamber vicinity are much greater for the Lubby2 law. The displacements indicated at the chamber contour are the reason that the alternative location in the anhydrite layer was more advantageous.